Plasmon-enhanced stimulated Raman scattering microscopy with single-molecule detection sensitivity - Cheng Zong (Nature Portfolio, 2019)
Stimulated Raman scattering (SRS) microscopy enables label-free chemical imaging at high speed, but has been limited by low sensitivity. Here, the authors demonstrate plasmon-enhanced SRS microscopy and achieve single molecule detection sensitivity.